What’s in a name?: Names and Titles in Pentecostal Ministries in Zimbabwe - Mapuranga, Tapiwa P. (Prophets, Profits, and the Bible in Zimbabwe: Festschrift for Aynos Masotcha Moyo, 2013)
The period beginning the late 1990s up until now, (2013) has seen the marked growth of Pentecostalism in Zimbabwe. This phenomenon will probably be still increasing beyond the contemporary period. This growth in Pentecostalism is witnessing a major shift in Christianity, with a notable increase in schisms and divisions within the church. This expansion of Pentecostalism has led to a notable increase in the appearance of churches with new names and titles for their leaders. A number of related questions may be asked. What is the significance of these names? Do these names of ministries in Pentecostalism signify some as more important or more spiritual than the others? Do these names in any way defy the common saying that ‘a rose by any other name would smell as sweet’? Though the concept of naming has received quite some significant scholarly attention, these studies have focused on names of literary characters, freedom fighters, dogs and death amongst other issues. None of these have discussed names of Pentecostal ministries in Zimbabwe. The thrust of this chapter is to analyse this perceived fissure in the study of names, as well as to clarify the significance of these names in the wake of the phenomenal expansion of prophetism in contemporary Zimbabwe. The chapter also links the emergence of titles of honour and power in the discussion of nomenclature in the wake of the increased visibility of Pentecostalism in the country.
free